2023
DOI: 10.5194/egusphere-2022-1453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thunderstorm Types in Europe

Abstract: Abstract. Lightning characteristics in all seasons are investigated across Europe because it is observed that lightning strikes to tall infrastructure have no or only a weak annual cycle whereas lightning in general has a pronounced annual cycle. Using cluster analysis on ERA5 reanalysis data and EUCLID lightning data, two major thunderstorm types are found: Wind-field thunderstorms characterized by increased wind speeds, strong updrafts, and high shear occurring mainly in winter. And mass-field thunderstorms … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Lightning formation is explained by the non-induction theory (Reynolds et al 1957;Takahashi 1978). A recent study conducted by (Morgenstern et al 2023) found that winter thunderstorms are characterized by increased wind speeds, strong updrafts, and high shear. While, ( Van Mai et al 2022) in a study applying lightning location data and human-observed thunderstorm day observations found that the majority of lightning occurs in the monsoon season (April-September), peaking in May and pointed that the lightning activity is very modest in October-March.…”
Section: Introductionmentioning
confidence: 99%
“…Lightning formation is explained by the non-induction theory (Reynolds et al 1957;Takahashi 1978). A recent study conducted by (Morgenstern et al 2023) found that winter thunderstorms are characterized by increased wind speeds, strong updrafts, and high shear. While, ( Van Mai et al 2022) in a study applying lightning location data and human-observed thunderstorm day observations found that the majority of lightning occurs in the monsoon season (April-September), peaking in May and pointed that the lightning activity is very modest in October-March.…”
Section: Introductionmentioning
confidence: 99%